HEMATOLOGICAL PROFILE IN PREGNANT WOMEN ATTENDING AL-FALAH GENERAL & EYE HOSPITAL IN BAHAWALPUR, PUNJAB, PAKISTAN - Muhammad Armish Mehdi; Ghulam Murtaza; Amjad Ali; Uzair Hussain; Muhammad Habibullah; Waqas Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
Background: Pregnancy entails significant physiological changes, including alterations in hematological parameters. Understanding these changes is crucial for maternal and fetal health. Objective: This cross-sectional study aimed to investigate the hematological characteristics of pregnant women, focusing on age distribution, blood group prevalence, and abnormal hematological parameters. Methods: A total of 100 pregnant females aged 16 to 48 years with gestational periods ranging from 8 to 40 weeks were included in the study conducted at Al-Falah General & Eye Hospital in Bahawalpur, Pakistan. Blood samples were collected and analyzed for complete blood count using an automatic hematological analyzer. Results: The majority of participants (40%) fell within the age range of 25 to 34 years, with B Positive being the most prevalent blood group. Anemia was observed in 51% of pregnant women, with varying levels of abnormality in parameters such as Hematocrit, Total Red Blood Cell Count, and Mean Cell Volume. However, Total Leukocyte Count and Platelets generally showed normal levels. Analysis of age distribution within each blood group revealed diverse patterns, suggesting potential age-related variations in hematological parameters. Conclusion: Monitoring hematological parameters during pregnancy is essential for ensuring maternal health and well-being. Further research is warranted to explore underlying factors contributing to observed variations and their implications for maternal and fetal outcomes.